2008
DOI: 10.1007/s11705-008-0057-5
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation time/temperature dependence of thermoplastics-modified thermosetting systems

Abstract: The cure-induced phase separation processes of various thermoplastics(TP)-modified thermosetting systems which show upper critical solution temperature (UCST) or lower critical solution temperature (LCST) were studied with emphasis on the temperature dependency of the phase separation time and its potential application in the cure time-temperature processing window. We found that the phase separation time/temperature relationship follows the simple Arrhenius equation. The cure-induced phase separation activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…SCs have a significantly lower critical concentration threshold for precipitation from organic solvents in comparison to their homochiral counterparts. Therefore, these l - and d -interactions lead to the self-assembly of stable SC nuclei, which then start to grow. , There are several studies on various materials that self-assemble into nanostructures, for example, on proteins but also on phase separations of copolymers and polymer blends. …”
Section: Resultsmentioning
confidence: 99%
“…SCs have a significantly lower critical concentration threshold for precipitation from organic solvents in comparison to their homochiral counterparts. Therefore, these l - and d -interactions lead to the self-assembly of stable SC nuclei, which then start to grow. , There are several studies on various materials that self-assemble into nanostructures, for example, on proteins but also on phase separations of copolymers and polymer blends. …”
Section: Resultsmentioning
confidence: 99%
“…In these processes, polymer synthesis and shaping take place in a single operation, which involves the conversion of liquid monomers and/or polymers into solid crosslinked polymers. [13][14][15][16][17] Very few systematic studies have been reported on the evolution of rheology in thermoset/thermoplastic (TS/TP) systems; [18][19][20][21] most of the studies are focused on final mechanical properties. The typical isothermal curing of thermoset/thermoplastic based blends is accompanied by the polymerization shrinkage and an increase in complex viscosity due to vitrification of the thermoset-rich phase.…”
Section: Introductionmentioning
confidence: 99%